Efeito agudo do aprimoramento do desempenho pós-ativação (PAPE) a partir do Squat Jump, Drop Jump e Alongamento Dinâmico no Special Wrestling Fitness Test (SWFT) para atletas de Luta Olímpica - COSTA, Marcus Vinicius da (Universidade Federal do Pará, 2025)
Warming up is an important part of an athlete's preparation, especially before a competition. Combat sports, such as wrestling, require high levels of muscular power during combat. Inducing Post-Activation Performance Enhancement (PAPE) before competition can benefit the athlete by enhancing their muscular power levels. To induce PAPE it is necessary to define a conditioning activity to be used, in this sense the objective of the present investigation was to compare the acute effect of Post-Activation Performance Enhancement (PAPE) from the squat jump (SJ), drop jump (DJ) and Sound stretching (AD) in the Special Wrestling Fitness Test (SWFT) in senior Olympic wrestling athletes. To this end, 20 adult male participants, aged between 23 and 35 years old, voluntarily participated in this research. Each participant underwent four visits, which were organized as follows: 1) familiarization; between 2 and 4) SWFT protocol and protocol for each conditioning activity. The conditioning activities were randomized, including squat jump, drop jump and dynamic stretching. Each visit had a minimum interval of 48 hours. The SWFT protocol was performed before and after each conditioning activity. Data were analyzed with ANOVA-MR. It was found that the SWFT index for both vertical jumps were similar and lower than in AD, demonstrating that the performance of vertical jumps, as a conditioning activity, in PAPE were better (p<0.001). Even so, the interval time used of 3 minutes was enough to enhance the fighters' performance in vertical jumps, but not in AD. In each conditioning activity, the number of throws performed pre- and post-SWFT reduced over the three series (p<0.001). However, the SJ and the DJ in the post-SWFT had a greater number of throws made, while in the AD the number of throws was lower than in the pre-SWFT (p<0.001). Based on these findings, it is possible to infer that both vertical jumps promote PAPE with a minimum interval of 3 minutes, while AD does not. Therefore, using vertical jumps during warm-up strategies to enhance muscular power in wrestling athletes is a viable, easy and effective way.